Penerapan Digital Marketing sebagai Trategi Pemasaran pada Cafe Yamoke di Kabupaten Tana Toraja - Imelda Jesika Bura; Mey E. Limbongan; Lisa K. Wibisono (CV. Ulil Albab Corp, 2024)
This research aims to analyze the effectiveness of implementing digital marketing as a marketing strategy at Cafe Yamoke in Tana Toraja Regency. The research method used is qualitative research with a descriptive approach. Data collection techniques are carried out through interviews, observation and documentation. The results of this research show that Cafe Yamoke has implemented digital marketing using social media such as Instagram, Facebook and Tiktok. The application of digital marketing has shown effectiveness in increasing brand awareness, attracting new customers and increasing sales.